If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 12 = 7(2x + -3) Reorder the terms: 12 + 3x = 7(2x + -3) Reorder the terms: 12 + 3x = 7(-3 + 2x) 12 + 3x = (-3 * 7 + 2x * 7) 12 + 3x = (-21 + 14x) Solving 12 + 3x = -21 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 12 + 3x + -14x = -21 + 14x + -14x Combine like terms: 3x + -14x = -11x 12 + -11x = -21 + 14x + -14x Combine like terms: 14x + -14x = 0 12 + -11x = -21 + 0 12 + -11x = -21 Add '-12' to each side of the equation. 12 + -12 + -11x = -21 + -12 Combine like terms: 12 + -12 = 0 0 + -11x = -21 + -12 -11x = -21 + -12 Combine like terms: -21 + -12 = -33 -11x = -33 Divide each side by '-11'. x = 3 Simplifying x = 3
| 10x+2x=10x | | 5sinx-4=since | | 2s+4s=2s | | X-1/10=x-9/2 | | w-8.1=6.4 | | 1982.596=2*3.14*8.2*8.2+2*3.14*8.2*h | | t*3-8=9 | | 2x^3-10x^2-71x-9=0 | | a*6+8=13 | | 4n+73=5 | | 4x+6=-54-8 | | 3y=15-x | | -77=-++55 | | =(3-2)X+2Y+2 | | y=3.40x+2.20 | | 2x-4=86 | | ln(2x)-ln(3)=5 | | 3x+17=11x+47 | | 6x+106=2x+108 | | -2n^2+9=-7n | | =X+2Y+2 | | n-13=86 | | a^2-6a=9 | | c-28=51 | | -2x^2=-2-3x | | 35/7=p | | 3b-4/2 | | -21=9a-15-3 | | 7=g/8 | | 6b-(5-4b)=25 | | 3(x-3)+6=4x+3 | | -21=9a-15 |